Citizen science school project: influence of colour and configuration on insect visitors - Prendergast, Kit (2020)
This presentation provides an introduction to pollination, the main insect taxa that visit flowers, and how flower colour, and flowering patch configuration (clumped, isolated, homogeneous, heterogeneous) can be predicted to influence the numbers and types of insect visitors. This presentation then describes a simple experiment that can be performed to investigate the influence of colour and configuration on insect visitors, using artificial flowers. This presentation is targeted for school age children (approximately 8 years old to 13 years old). These experiments have been conducted across five schools in Australia led by a female PhD/Early Career Researcher, recipients of the Ecological Society of Australia and NSW Environment, Energy & Science award for Outstanding Outreach 2018 (Kit Prendergast, Amelie Vanderstock, Heather Neilly, Catherine Ross, and Vanessa Pirotta), supervised by Patrick Tegart.